PENGARUH WORK FROM HOME (WFH) TERHADAP KINERJA KARYAWAN - Catherine Angelia Paramban; Joan Yuliana Hutapea (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2022)
This research was conducted to determine the effect of Work from Home towards an employees performance. This research is aimed to find a better way for companies and employees alike to reap a successful working method without having physical contact. The method of this research is done by using questionnaire as the instruments. The sampling techniques is a non-probability sampling, the population of this study are all the managers of Johnson&Johnson, with a total sample of 20. Which was taken on certain period of time. The analysis used in this research are descriptive statistical analysis, correlation coefficient test, coefficient of determination test, t significant test and simple linear regression. The results showed that partially there was a positive and significant effect between Work from Home on employees performance.